2021
DOI: 10.3390/en14041137
|View full text |Cite
|
Sign up to set email alerts
|

Cyber Attacks in Transactive Energy Market-Based Microgrid Systems

Abstract: Due to the increasing integration of distributed energy generation in the electric grid, transactive energy markets (TEMs) have recently emerged to balance the demand and supply dynamically across the grid. TEM enables peer to peer (P2P) energy trading and brings flexibility by reducing users’ demand in the grid. It also enhances the system’s efficiency and reduces the pressure on electricity networks. However, it is vulnerable to major cyber attacks as users equipped with smart devices are participating auton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…A 2-layer DBN stacked through 2 RBMs holds a set of visible layers and 2 layers of hidden layers. If h (1) and h (2) denotes the state vectors of the hidden layer, v represents state vector of the visible layer, W (1) and W (2) indicates the matrix of the symmetrical weight, b (1) and b (2) signifies bias vectors of the hidden layers, and b (0) is the bias vectors of the visible layer.…”
Section: Load Prediction Using Dbn Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…A 2-layer DBN stacked through 2 RBMs holds a set of visible layers and 2 layers of hidden layers. If h (1) and h (2) denotes the state vectors of the hidden layer, v represents state vector of the visible layer, W (1) and W (2) indicates the matrix of the symmetrical weight, b (1) and b (2) signifies bias vectors of the hidden layers, and b (0) is the bias vectors of the visible layer.…”
Section: Load Prediction Using Dbn Modelmentioning
confidence: 99%
“…It carries several benefits, like decreasing environment pollution, lower the power cost of DERs holders, minimize cost, etc. [1]. Furthermore, DERs owners could transform from consumer to prosumer by trading their excess energy production to other users and grids.…”
Section: Introductionmentioning
confidence: 99%
“…In the digital transformation of energy industry, there are several potential risks, such as geomagnetic storms, malware, ransomware, phishing, botnets, etc. 48 For example, in 2015, Ukraine suffered a cyber-attack specifically on the power grid. The attacker used both the malware and the email phishing to obtain personnel credentials not only, but also attacked the substation's Supervisory Control and Data Acquisition system to prevent customers from getting the information about the outage.…”
Section: Security Risksmentioning
confidence: 99%
“…Such links can be indeed targeted by cyber attacks with the purpose of taking advantages in the energy market [7]. With respect to the energy market in microgrids, we mention the work of Dasgupta et al [28] that identified potential cyber-attacks in such systems as well as implications to smart grids. On the same line, and conversely to what happens in microgrids, the production or storage of energy lies in the same physical infrastructure as consumers; thus, control communications in active buildings can be exchanged through the existing network channel of the building.…”
Section: Introductionmentioning
confidence: 99%